SCIENTIFIC APPROACH OF 2013 CURRICULUM IMPLEMENTATION: A CASE STUDY IN A RURAL AND URBAN AREA OF SOUTH SULAWESI - Kartini Kartini (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
This study aimed at identifying and explaining the implementation of scientific approach of 2013 curriculum and exploring the teachers’ perception on the implementation of scientific approach of 2013 curriculum. This case study used interview and observation to collect data. All data were analyzed through a qualitative approach. The participants of the study were two English secondary school teachers in rural area (School A) located in Polombangkeng District, Takalar Regency, and urban area (School B) located in Tamalate District, Makassar. The study showed that both schools have implemented the scientific approach of 2013 curriculum well and the teachers basically understand the five stages of scientific approach. However, there were still shortcomings in some aspects found on their perceptions. These aspects of scientific approach principle are not fully aligned with the characteristics of the 2013 curriculum. Based on these results, the researcher concluded that the implementation of the scientific method of 2013 curriculum in seventh grade English subjects conducted by English teachers has not been fully functional as appropriate. Therefore, the practice of applying the scientific approach of 2013 curriculum requires an improvement in these aspects in order to achieve the objectives of the implementation of the 2013 curriculum.